2022
DOI: 10.3390/diagnostics12112874
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Pneumonitis: A Pictorial Review Based on the New ATS/JRS/ALAT Clinical Practice Guideline for Radiologists and Pulmonologists

Abstract: Hypersensitivity pneumonitis (HP) is a complicated and heterogeneous interstitial lung disease (ILD) caused by an excessive immune response to an inhaled antigen in susceptible individuals. Accurate diagnosis of HP is difficult and necessitates a detailed exposure history, as well as a multidisciplinary discussion of clinical, histopathologic, and radiologic data. We provide a pictorial review based on the latest American Thoracic Society (ATS)/Japanese Respiratory Society (JRS)/Asociación Latinoamericana del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Similar to our findings, the lymphocyte ratio in BAL was 19.18% in the fibrotic group, whereas it was 29.23% in the nonfibrotic group 25 . According to Dabir et al stated that VC and diffusion capacity decrease in both fibrotic and non‐fibrotic types, and decrease more, older, lymphocyte ratio lower, unknown antigen more common in fibrotic type 26 . Lacasse et al found that when classifying patients based on a combination of clinical features, imaging, and pathophysiology, those with a sub‐acute presentation were particularly difficult to define and that a two‐category model was a better fit.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our findings, the lymphocyte ratio in BAL was 19.18% in the fibrotic group, whereas it was 29.23% in the nonfibrotic group 25 . According to Dabir et al stated that VC and diffusion capacity decrease in both fibrotic and non‐fibrotic types, and decrease more, older, lymphocyte ratio lower, unknown antigen more common in fibrotic type 26 . Lacasse et al found that when classifying patients based on a combination of clinical features, imaging, and pathophysiology, those with a sub‐acute presentation were particularly difficult to define and that a two‐category model was a better fit.…”
Section: Discussionsupporting
confidence: 89%
“… 25 According to Dabir et al stated that VC and diffusion capacity decrease in both fibrotic and non‐fibrotic types, and decrease more, older, lymphocyte ratio lower, unknown antigen more common in fibrotic type. 26 Lacasse et al found that when classifying patients based on a combination of clinical features, imaging, and pathophysiology, those with a sub‐acute presentation were particularly difficult to define and that a two‐category model was a better fit. Cluster 1 comprised patients with recurrent and systemic symptoms including chest tightness, shortly after antigen exposure, with a greater likelihood of normal imaging, and Cluster 2 comprised advanced fibrotic disease with inspiratory crackles, clubbing, and low lung function.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental aspect that deserves high attention to avoid over-diagnosis leading to over-treatments is that a high number of individuals exposed to an offending antigen develop an antigen-specific immune response, limited to the presence of serum IgG antibodies and an increased number of lymphocytes in the lung, without ever subsequently developing the pulmonary disease. This premise remains crucial for understanding that the host's response is fundamental to the disease's development [5,6].…”
Section: Definition Epidemiology the "Transition Of Classification" C...mentioning
confidence: 99%
“…Identifying the responsible antigen is more challenging, and the functional state is generally more compromised. BAL may reveal a pattern of lower or absent lymphocytosis, and sometimes an increase in neutrophils and eosinophils, characteristic of a worse prognosis phenotype [5].…”
Section: Definition Epidemiology the "Transition Of Classification" C...mentioning
confidence: 99%
“…A combination of clinical symptoms, exposure history, and imaging or lung function testing is usually used to make the diagnosis of HP. Treatment may include avoiding further contact with moldy dust or the triggered stimulus, as well as administering corticosteroids or other immunosuppressive medications [ 1 ].…”
Section: Introductionmentioning
confidence: 99%